Spirituality of Ageing for Human Flourishing:: Towards a New Paradigm of Economics (The Macau Ricci Institute Journal, 2020)
Pope Francis shows special concern for the marginalized and the weakest. The elderly are among the most vulnerable and less valuable in the society due to their declining value in productivity and economics. To address the mission of Francis and his vision of hope for the entire human family, I would like to propose a new paradigm for the spirituality of ageing, based on his papal teaching of Integral Human Development (IHD), especially its intercultural dimension.